Models of Cognitive Processes as Depicted in the Sutta Literature - Neupane, Fanindra Kumar (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: Buddhism renders all the miseries and sorrows in human beings to the evils inherent in the cognitive process. In the Pāli Commentaries and Sub-commentaries, a comprehensive model of cognitive process is discussed in the terminology of Citta-Vīthi, however, this concept is depicted in the original Sutta, Vinaya, and Abhidhamma Canonical texts at the very basic level. In such teachings, knowledge acquired through sense perception is taken as the phenomena leading towards sorrow and misery. Objective: The objective of the study is to explore the models of five aggregates, six āyatana and eighteen dhātus, dependent origination, and thought proliferation in Sutta teachings. Methodology: This research work has adopted the critical thinking skill research method to explore the cognitive process models depicted in the Sutta Literature. Result: From such study, it has been found that in Sutta teachings cognitive process is depicted as the models of five aggregates, six āyatana and eighteen dhātus, dependent origination, and thought proliferation. Conclusion: The teachings of the Buddha always focus on the rational understanding (sammā-diṭṭhi) of the subject matter how the senses work and how the misery entails in these processes. Thus, it is important to explore the models of cognitive processes depicted in the original Sutta literature. For that purpose. At the end of this research, a conclusion is drawn that every event of the cognitive process begins from a simple sensation process and proceeds by degrees to a discriminative apprehension of the sense object.